A capacious approach to creative citizenship: Implications for policy - Hargreaves, I.; Hartley, John (2016)
The book’s first ten chapters are summarised, drawing attention to policy relevant or otherwise actionable strategies to enhance the scale and value of creative citizenship. A dialogue with four UK political think tanks is highlighted, drawing attention to points of agreement between creative citizenship and mainstream political thinking, along with tensions. Reflections are offered upon aspects of the work of the UK coalition government (2010–2015) and the opening phase of its successor (2015–). A sample policy agenda for one of the areas of study in the creative citizens project – hyperlocal journalism – is offered as an illustration of the readiness with which action programmes to support aspects of creative citizenship can be attempted. An indication of relevant policy directions with regard to creative citizenship’s implications for education and the economy is given. The challenges attaching to a growth of creative citizenship in the context of international polities such as the European Union is discussed. The conclusion is reached that creative citizenship offers an important and salient concept in the context of well-established but still growing global social media. The case for the unbinding of the creative citizen is strong.